Implementasi Nilai-nilai Tazkiyatun Nafs Dalam Pendidikan Islam Kontemporer Perspektif Imam al-Ghazali - Sahduari Sahduari; Abdullah Abdullah; Saiful Lutfi (Jayapangus Press, 2026)
This study aims to analyze the implementation of tazkiyatun nafs values in contemporary Islamic education from the perspective of Imam al-Ghazali, specifically within the book Ayyuhal Walad. The primary background of this research is the moral crisis, materialism, and the dichotomy of knowledge within modern educational systems. The method employed is qualitative library research with a descriptive-analytical approach, incorporating textual, contextual, and intertextual interpretations of al-Ghazali's thoughts. The results indicate that tazkiyatun nafs serves as a practical-applicative methodology in seeking knowledge, rather than merely an ethical theory. Three systematic stages relevant to contemporary education were identified: Takhalli (purification from blameworthy traits such as intellectual arrogance and worldly orientation), Tahalli (internalization of sincerity and respect for knowledge and teachers), and Tajalli (the actualization of spiritual values in real-world behavior). The gap analysis reveals that current education suffers from axiological and epistemological dryness, where highly educated graduates often lack moral integrity. Al-Ghazali provides a solution through five primary advisory points in Ayyuhal Walad, including time optimization and the integration of knowledge with deeds. The conclusion emphasizes that the implementation of tazkiyatun nafs is a fundamental solution to address the spiritual crisis in modern Islamic education. Education must not only focus on Intelligence Quotient (IQ) but must be rooted in soul purification to cultivate insan kamil (the perfect human). Practical recommendations for Islamic educational institutions include integrating a Sufism-based character curriculum that prioritizes role modeling and the process of heart purification as the core foundation of all learning activities to navigate increasingly complex contemporary challenges.